2002
DOI: 10.1086/340418
|View full text |Cite
|
Sign up to set email alerts
|

Association between Larger Thymic Size and Higher Thymic Output in Human Immunodeficiency Virus–Infected Patients Receiving Highly Active Antiretroviral Therapy

Abstract: To examine the impact of thymic size on immune recovery in patients with human immunodeficiency virus (HIV) infection, the thymus was visualized, using computed tomographic scans, in 25 HIV-infected patients who had received highly active antiretroviral therapy (HAART) for 6-18 months and had levels of viremia <500 copies/mL. For comparison, 10 control subjects were included in the study. Total and naive CD4+ cell counts were determined by flow cytometry. To determine thymic output, the number of CD4+ cells co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 34 publications
(64 reference statements)
1
78
0
4
Order By: Relevance
“…In first weeks after initiating the treatment there is a release of memory cells from lymphoid tissue to peripheral blood, 30 but later there is an increase of memory cells in both compartments due to a decrease of CD4 þ cells proliferation and death. 6,7,14,31 However, the treatment with HAART also produces an increase of newly generated naive cells due to an increase of thymic production [14][15][16] and/or a peripheral expansion of naive cells. 32 In our study, we have observed an increase of both naive and memory cells in interfollicular areas of the lymphoid tissue, after 12 and 36 months of HAART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In first weeks after initiating the treatment there is a release of memory cells from lymphoid tissue to peripheral blood, 30 but later there is an increase of memory cells in both compartments due to a decrease of CD4 þ cells proliferation and death. 6,7,14,31 However, the treatment with HAART also produces an increase of newly generated naive cells due to an increase of thymic production [14][15][16] and/or a peripheral expansion of naive cells. 32 In our study, we have observed an increase of both naive and memory cells in interfollicular areas of the lymphoid tissue, after 12 and 36 months of HAART.…”
Section: Discussionmentioning
confidence: 99%
“…Under HAART, the CD4 þ T cell increase is determined by a decrease of dying T cells, 6,7,14 and also by thymic output. 15,16 These events are associated with a suppression of the plasma viral load and an increase of CD4 þ T lymphocytes in peripheral blood. However, in spite of this improvement, after interrupting HAART there is a rebound of the plasma viral load again.…”
mentioning
confidence: 99%
“…3,[8][9][10][11][12][13][14][15][16] Similarly, normal TREC contents have been observed after successful ART. 17 However, because introducing only a few TREC-holding cells in a virtually empty CD4 T-cell pool may suffice to increase the average TREC content, it is debatable whether rapid normalization of CD4 TREC contents truly reflects increased thymic output.…”
Section: Introductionmentioning
confidence: 86%
“…Although the thymus was once thought to be active only early in life, a thymic reserve appears to persist into adulthood (11,12), and its function may increase in the setting of lymphopenia induced by chemotherapy (13,14) or HIV-1 disease (15). Studies of T cell reconstitution after lymphopenia demonstrate that a greater abundance of thymic tissue is associated with improved recovery of total and naive CD4 + T cells (2,(16)(17)(18)(19)(20), increased frequency of TCR rearrangement excision circles (TRECs) (11,21,22), and increased TCR repertoire diversity (21,23). Thus, therapeutic agents that stimulate thymic function may improve the quantity and quality of immune reconstitution during HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%